IMPLEMENTASI SELF-REGULATED LEARNING DALAM MENANGANI KESULITAN BELAJAR SISWA UNDERACHIEVER - Anikmatul Khoiroh (CENDEKIA, 2021)
The purpose of this research is to know Self-Regulated Learning Implementation in Dealing with Student Learning Difficulties Underachiever. This research is a descriptive qualitative research with field research type. Research subjects of eighth grade students who have experienced underachiever. Data were collected using interview technique, observation and documentation. Data analysis techniques used are interactive data analysis and checked with triangulation. The results showed that the treatment used to improve self-regulated learning with motivational training or commonly called Achieverment Motivation Training (AMT), tutoring, learning assistance program.